2010
DOI: 10.1167/iovs.09-5035
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Visual Field Sensitivity and Macular Ganglion Cell Complex Thickness as Measured by Spectral-Domain Optical Coherence Tomography

Abstract: GCCT, determined by SD-OCT, showed correlation to MS of a strength similar to that demonstrated between MS and pRNFLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 31 publications
7
80
0
1
Order By: Relevance
“…A thinner GCC was associated with lower retinal sensitivity as shown earlier in glaucoma cases. 24,25 As the GCC thickness changed in the area corresponding to the ILM peeled area, measuring not only central visual acuity but retinal sensitivity seems important to evaluate postoperative macular function after ILM peeling.…”
Section: Discussionmentioning
confidence: 99%
“…A thinner GCC was associated with lower retinal sensitivity as shown earlier in glaucoma cases. 24,25 As the GCC thickness changed in the area corresponding to the ILM peeled area, measuring not only central visual acuity but retinal sensitivity seems important to evaluate postoperative macular function after ILM peeling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that GCC thickness was significantly lower in glaucomatous eyes with visual field defects than in healthy eyes [13,14]. A number of studies report a high correlation between global visual field sensitivity and GCC in glaucomatous subjects using SD-OCT [15,16].…”
Section: Introductionmentioning
confidence: 97%
“…These anatomical correlates are known to diminish in thickness and volume as a result of glaucoma (monkey 18,19 , human [20][21][22][23][24][25][26][27][28][29][30][31][32][33] ). We used a Heidelberg spectral domain -optical coherence tomography (SD-OCT, Spectralis ® ) device to quantitatively measure these structures noninvasively in the living human eye.…”
Section: Fields Of Research (For) Classificationmentioning
confidence: 99%
“…However, this relationship may not be strictly linear such that early in the glaucomatous disease process, visual field performance tends to be better than that suggested from thinning of the retina and RNFL. (monkey 18,19 , human [20][21][22][23][24][25][26][27][28][29][30][31][32][33] ) By the time visual field defects are detected, up to 30% of the optic nerve can be damaged. 13,14 It is unclear why visual field performance tends to be more robust and resistant to change compared to optic nerve head structure in some patients with glaucoma.…”
Section: Secondary Study Endpointsmentioning
confidence: 99%
See 1 more Smart Citation